High performance building facade via EM structures - Ng, Hsin Inn (2017)
With the depletion of the world’s natural resources due to its abundant usage as well as the catastrophic effects such usage brings to the environment, there is a need for alternatives to prolong its depletion and to mitigate the negative impacts brought about to the environment. With the rapid increase in the development of wireless communication in today’s world, the use of the Radio Frequency (RF) in various fields has gained a substantial amount of popularity. As such, the concept of RF energy harvesting using antennas has gradually established a growing prevalence in an attempt to develop new energy sources to replace the use of natural resources. This report focuses on RF energy harvesting using a meta-resonator antenna. In this report, the entire process of creating a meta-resonator antenna is presented. Firstly, a detailed and comprehensive background research is done to better understand the different parameters and features of an antenna, and also the criteria and standards that constitute to the good performance of an antenna. The modelling of the proposed antenna is then adopted using the Computer Simulation Technology (CST) simulation software before simulating and optimizing using the same software to obtain and evaluate the performance of the modelled antenna. Upon achieving an antenna of desired performance, it is then drawn using Pads Layout software before being fabricated into a prototype on a Printed Circuit Board (PCB). Lastly, the fabricated prototype is tested to obtain experimental results to verify the simulated results.